LAY UP SHOOT EXERCISE SKILL MODEL OF BASKETBALL BASED GAME FOR BEGINNER AGE 12-14 YEARS - Jovana Renaldy Gumay; Firmansyah Dlis; Ika Novitaria Maharani (Journal Physical Education, Health and Recreation, 2018)
The goal to be achieved from this research and development is to produce a model model of game play basketball skill-based skill training for 12-14 year olds. This research and development is conducted to get information about the development and implementation of model of game-based basketball lay up shoot skill training for 12-14 years old and to know the effectiveness of theresulting model. This research uses Research & Development (R & D) method from Borg and Gall. Subjects in this study were junior high school students who followed extracurricular basketball consisting of 60 children. The steps in this study are: needs analysis, expert evaluation (initial product evaluation), small group trial, and field testing. The model effectiveness test uses the basketball lay up shoot skill test which is used to know the level of lay up shoot ability of the child before and after the treatment of lay up shoot skill training model developed. Preliminarytests performed obtained level of dribbling ability of students is 3.473684. After given treatment dribbling exercise model obtained level of dribbling ability of students 10.78947. On the significant test the difference with spss 16 obtained mean = -7.31579 shows the difference of pretest results and post-test results, t-hitung = -55.751 df = 37 and p-value = 0.00 <0.05 which means there is a significant difference between before and after being given a modeling practice of  skill lay up shoot basketball. The model of game-based basketball lay up shoot skills training for 12-14 year olds is effective for improving basketball lay up shoot skills for 12-14 year olds.